Inquiries into Malaysia's socio-technical disasters: recommendations and lessons learnt - Said, Aini Mat; Ahmadun, Fakhru'l-Razi; Kadir, Razali Abdul; Daud, Mohamed (Blackwell Publishing, 2009)
Most democratic countries hold inquiries into disasters. One of their key functions is to establish the cause of an event and to learn lessons in order to prevent a recurrence. In addition, they offer an opportunity for communal catharsis, permitting the public to vent anger, distress and frustration and to exert pressure for policy changes. Malaysia has experienced six landmark socio-technical disasters since 1968, which resulted in the proposal or amendment of various safety/emergency acts and regulations. The authors used a grounded theory approach utilising a constant comparative method to analyse the recommendations made by the inquiries into these events. Data indicate that social and technical recommendations comprise 85 and 15 per cent, respectively, of the total recommendations made by the inquiry committees. This paper offers suggestions for improving the management of inquiry tribunals, as they will remain a valuable source of information for society and corporations to learn from past incidents.